2004
DOI: 10.1136/vr.155.12.349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the appicatoion of veteroinary judgement in the pre‐emptive cull of contiguous premises during the epidemic of foot‐and‐mouth disease in Cumbria in 2001

Abstract: This paper presents a detailed analysis of the application of contiguous culling in Cumbria between May 1 and September 30, during the outbreak of foot-and-mouth disease in 2001. The analysis shows that the application of veterinary risk assessment and judgement identified and removed groups of susceptible stock which were at risk of direct transmission of infection and avoided infected animals being left that might have spread the disease. When compared with an automatic contiguous cull, fewer culls were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
0
26
0
1
Order By: Relevance
“…Therefore it is possible that salient diseases and experiences may drive current understanding and interpretation of terms such as biosecurity. It has been shown that FMD risks from indirect contacts can be greater than the risk from direct contacts [45], so perhaps producers in the study area were aware of this. Prevention of indirect contacts may be easier to undertake and less expensive than prevention of direct contacts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is possible that salient diseases and experiences may drive current understanding and interpretation of terms such as biosecurity. It has been shown that FMD risks from indirect contacts can be greater than the risk from direct contacts [45], so perhaps producers in the study area were aware of this. Prevention of indirect contacts may be easier to undertake and less expensive than prevention of direct contacts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, achieving disease-free status as quickly as possible or minimizing spatial spread can rarely be accomplished using conservative strategies (13,17). Also at issue is the unresolved argument about the extent to which blanket recommendations for control should be modulated by local veterinary knowledge (10,12). From a simply technical point of view, our model could be criticized on two counts.…”
Section: Discussionmentioning
confidence: 99%
“…Fakta ini lebih besar dari perkiraan para petugas lapangan dari pihak pemerintah yang hanya memperkirakan 3 hingga 4 yang mampu dilaksanakan. Hal ini sangat tidak efektif jika dibandingkan dengan pendapat Honhold et al (2004) yang menyatakan bahwa sebuah program pengendalian penyakit ternak akan efektif mencapai tingkat keberhasilan jika 99,99% program terlaksana dengan baik. Fakta lain dari Sumiarto et al (2006) menyatakan bahwa efektivitas pelaksanaan kebijakan strategi pengendalian flu burung oleh Dinas Peternakan di Jawa mencapai 88,9%, lebih lanjut juga diungkapkan bahwa hal ini belum efektif karena belum mencapai 99,99%.…”
Section: Efektivitas Pelaksanaan Kebijakan Pengendalian Aiunclassified